Fluid Management in Pediatric Urology: A Review of the Literature and Call for a Change in Practice. Issue 6 (November 2015) - Carpenter, Christina P.; Iskander, Andrew; Hausdorff, Mark; Stock, Jeffrey A.
Abstract : Introduction: : We investigate the intravenous fluid ordering practices of pediatric urologists. We also provide evidence for the use of isotonic fluids and, thus, establish a new standard for the field. Methods: : An online questionnaire was distributed via the listserve of the American Academy of Pediatrics Section on Urology. For 3 patient scenarios the respondents were asked to select which intravenous fluid they would prescribe and which infusion rate they would choose. Fluid choices were listed as lactated Ringer solution, normal saline, 0.45% normal saline, 5% dextrose in lactated Ringer solution, 5% dextrose in 0.45% normal saline, none and other (with write‐in option). Infusion rate choices were listed as maintenance (defined according to the Holliday‐Segar 4‐2‐1 nomogram), ½x maintenance, 1.5x maintenance, 2x maintenance and other (with write‐in option). A final question probed physician reason(s) for selections. Results: : The survey had a 35% response rate. The majority of respondents use 5% dextrose in 0.45% normal saline, and the most common infusion rate is 1.5x maintenance. Additionally, choices for fluid use and infusion rate were based on a combination of physician training and personal experience. Only 13% of respondents stated that they routinely avoid isotonic fluids. A PubMed® literature search demonstrated that the general pediatric and surgical specialty literature discourages hypotonic fluids and favors the judicious use of isotonic hydration and dextrose. Conclusions: : A change in pediatric urology needs to occur such that isotonic fluids at maintenance rate become the standard, with the addition of dextrose and/or increasing of rate only for carefully selected patients.